Pengaruh Kompensasi dan Motivasi terhadap Kinerja Guru Tidak Tetap pada Sekolah Menengah Atas (SMA) Negeri 1 Kabupaten Bungo - Meyda Milenitha (Jurnal bintang manajemen, 2025)
This research aims to determine the effect of Compensation and Motivation on the Performance of Non-Permanent Teachers at SMA Negeri 1 Bungo Regency. The population in this study consists of all Non-Permanent Teachers, and the research sample includes 39 respondents using the saturated sampling technique. (total sampling). From the data processing using SPSS, the results show that, partially, Compensation has a positive and significant effect on the Performance of Non-Permanent Teachers at SMA Negeri 1 Bungo Regency, and Motivation has a positive and significant effect on the Performance of Non-Permanent Teachers at SMA Negeri 1 Bungo Regency. Meanwhile, simultaneously, Compensation and Motivation have a positive and significant effect on the Performance of Non-Permanent Teachers at SMA Negeri 1 Bungo Regency.